E-093 Geographical variation in the decision to proceed with endovascular treatment under 'current' and 'ideal' settings. (22nd July 2019) - Kashani, N; Ospel, J; Almekhlafi, M; Wilson, A; Rabinstein, A; Kunz, W; Campbell, B; Foss, M; Turjman, F; Fischer, U; Baxter, B; Sylaia, P; et al.
Abstract : Background: In light of multiple trials showing efficacy of mechanical thrombectomy with highest level of supporting evidence, limited information is available on how treating physicians around the world make decisions in real-life regarding patient selection for (EVT). Regional differences exists where for the same patient presentation and attributes, the decision to treat endovascularly could differ based on local practice and resource settings. In this study we seeked to determine the effect of regional and country specific factors on endovascular treatment and how those decisions could differ in a simulated 'ideal' setting if resources were not to be constrained. Methods: We conducted a multidisciplinary survey of Neurosurgeons, Neurointerventional Radiologists, Neurologists, and other clinicians involved in acute stroke care around the world in an effort to understand prevailing approaches in management of stroke using a case-based approach (n=603 from 38 countries). The participants were presented with 10 randomly assigned cases with varying patient characteristics. Respondents were asked which treatment they would selected for each patient in their 'current' practice setting versus 'ideal' conditions. The rate of EVT selection was calculated and compared across different world countries. The propensity to add EVT under 'ideal' conditions were compared across geographic regions taking into account physician age, experience, specialty, and academic practice setting. Results: In the case scenarios 75.5% of the respondents proceeded with EVT under 'current' practice setting and were stratified into 7 geographic regions (6070 responses). Regions with relatively lower than average positive rates in proceeding with EVT were South America (58% n=24) and South Asia (60.5% of n=24), compared to 78% global. Average age of the treating clinicians in South America was 37.3 versus 44.8 global average (H=373.6; p<0.001) which reflected number of years in practice 9.4 vs. 14.2 yrs average (H=637.1; p<0.001). When considering an 'ideal' setting, clinicians in South America 18% and South Asia 19.5% were most likely to add EVT versus the 6.9% global average. Conclusion: In the selection of patients to undergo endovascular treatment, there exists a significant difference in rate of EVT procedures performed across countries and regions in the world reflecting local resources and practice settings. The decision to proceed with EVT reflects factors such as center volumes and clinician age & experience as contributing factors with younger clinicians in centers with lower volumes being more likely to consider EVT in an 'ideal' setting. Disclosures: N. Kashani: None. J. Ospel: None. M. Almekhlafi: None. A. Wilson: None. A. Rabinstein: None. W. Kunz: None. B. Campbell: None. M. Foss: None. F. Turjman: None. U. Fischer: None. B. Baxter: None. P. Sylaia: None. S. Yoshimura: None. J. Heo: None. B. Kim: None. M. Hill: None. G. Saposnik: None. B. Menon: None. M. Goyal: None.